A Comprehensive Antimicrobial Activity Evaluation of the Recombinant Microcin J25 Against the Foodborne Pathogens Salmonella and E. coli O157:H7 by Using a Matrix of Conditions - Yu, Haitao; Li, Ning; Zeng, Xiangfang; Liu, Lu; Wang, Yuming; Wang, Gang; Cai, Shuang; Huang, Shuo; Ding, Xiuliang; Song, Qinglong; Qiao, Shiyan (Frontiers in Microbiology, 2019)
Natural microcin J25 (MccJ25) represent promising alternatives to traditional antibiotics for the treatment of drug-resistant infections. However, little is known about the antibacterial activity of recombinant MccJ25 against foodborne pathogens. Here, the activity of recombinant MccJ25 was examined using a matrix of conditions in order to assess the efficacy of recombinant MccJ25 as a mitigation against foodborne pathogens, Salmonella species and Escherichia coli (E. coli) O157. Results showed that recombinant MccJ25 displayed excellent antimicrobial activity against these foodborne pathogens, including clinical isolates of Salmonella and E. coli, as well as clinical antibiotic-resistant Salmonella and E. coli isolates with different minimal inhibitory concentrations. In addition, antimicrobial activity curves and live/dead assay evidenced that recombinant MccJ25 harbors strong bactericidal activity against salmonella and E. coli O157. Notably, recombinant MccJ25 also had great potency and induced fast mortality against different growth phase of Salmonella and E. coli. The stability analysis results showed that the activity of recombinant MccJ25 was not influenced by temperatures as high as 121°C. Varying the pH from 2.0 to 9.0 did not appear to affect the activity of recombinant MccJ25. Under the challenge of several proteases, simulated gastrointestinal fluids and serum, recombinant MccJ25 still maintained exceptionally strong antimicrobial activity. Significant reductions in S. Pullorum levels were also achieved in food biological environments, such as milk, egg and meat. Moreover, we demonstrated that recombinant MccJ25 appeared to act by inducing membrane breaks, thinning, and disintegration in the S. Pullorum cytoplasmic membrane. Taken together, these results indicated that recombinant MccJ25 could be an effective alternative for mitigating and prevention of Salmonella and E. coli infection in food, animal and agriculture applications.